Community Ltd. and the spirit of ethno-enterprise : exploring cultural branding and incorporation among the Makuleke - Van Zyl, Izak Jakobus (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MA (Sociology and Social Anthropology))--University of Stellenbosch, 2010.